Fiscal multipliers in the COVID19 recession. (September 2022) - Auerbach, Alan; Gorodnichenko, Yuriy; McCrory, Peter B.; Murphy, Daniel
Abstract: In response to the record-breaking COVID19 recession, many governments have adopted unprecedented fiscal stimuli. While countercyclical fiscal policy is effective in fighting conventional recessions, little is known about the effectiveness of fiscal policy in the current environment with widespread shelter-in-place ("lockdown") policies and the associated considerable limits on economic activity. Using detailed regional variation in economic conditions, lockdown policies, and U.S. government spending, we document that the effects of government spending were stronger during the peak of the pandemic recession, but only in cities that were not subject to strong stay-at-home orders. We examine mechanisms that can account for our evidence and place our findings in the context of other recent evidence from microdata.